The Influence of Principal Leadership and Work Motivation on Kindergarten Teacher Discipline - Rahayu, Sri; Yuliejatiningsih, Yovita; Maryanto (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This study analyzes the influence of principal leadership and work motivation on kindergarten teacher discipline in Temanggung District. Teacher discipline plays a crucial role in maintaining a conducive and high-quality learning environment. Effective principal leadership and strong work motivation are essential factors in fostering teacher discipline, ensuring professionalism, and improving educational outcomes. This research employs a quantitative approach using a survey method. The study sample consists of 106 kindergarten teachers selected through proportional random sampling. Data were collected using a validated and reliable questionnaire, then analyzed using simple and multiple regression techniques. The findings reveal that principal leadership significantly influences teacher discipline, with a t-value of 5.923 and a contribution of 43.3%. Work motivation also has a significant effect, with a t-value of 3.241 and a contribution of 36.2%. Simultaneously, these two factors contribute 59.8% to teacher discipline. These results emphasize the importance of strengthening principal leadership and implementing strategies to enhance teacher motivation. Schools should focus on leadership training programs and motivation-enhancing initiatives to create a more disciplined and professional educational environment.